2020
DOI: 10.1111/cpr.12959
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of AMPA receptor subunit GluA1 in synaptic plasticity: Implications for Alzheimer's disease

Abstract: It is well established that GluA1 mediated synaptic plasticity plays a central role in the early development of AD. The complex cellular and molecular mechanisms that enable GluA1‐related synaptic regulation remain to fully understood. Particularly, understanding the mechanisms that disrupt GluA1 related synaptic plasticity is central to the development of disease‐modifying therapies which are sorely needed as the incidence of AD rises. We surmise that the published evidence establishes deficits in synaptic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 172 publications
2
30
0
Order By: Relevance
“…Synaptic pathology is another key neuronal phenotype of AD, but this slowly evolving pathology begins as synaptic dysfunction that is thought to percolate years before the overt and wholesale killing of synapses and then neurons ( Selkoe, 2002 ). A loss of glutamate receptors is what typifies this early synaptic stage of neurodegeneration ( Yasuda et al, 1995 ; Wakabayashi et al, 1999 ; Qu et al, 2021 ), and we extend previous work in the hippocampal slice ( Temkin et al, 2017 ) to show that this phenotype is regulated by retromer in the intact hippocampus. With respect to tau pathology, retromer has been linked to intraneuronal tauopathy in mouse models ( Carosi et al, 2021 ; Vagnozzi et al, 2019 ) or in IPS neurons derived from patients with AD ( Young et al, 2018 ), but only on the background of preexisting intraneuronal pathology.…”
Section: Discussionsupporting
confidence: 76%
“…Synaptic pathology is another key neuronal phenotype of AD, but this slowly evolving pathology begins as synaptic dysfunction that is thought to percolate years before the overt and wholesale killing of synapses and then neurons ( Selkoe, 2002 ). A loss of glutamate receptors is what typifies this early synaptic stage of neurodegeneration ( Yasuda et al, 1995 ; Wakabayashi et al, 1999 ; Qu et al, 2021 ), and we extend previous work in the hippocampal slice ( Temkin et al, 2017 ) to show that this phenotype is regulated by retromer in the intact hippocampus. With respect to tau pathology, retromer has been linked to intraneuronal tauopathy in mouse models ( Carosi et al, 2021 ; Vagnozzi et al, 2019 ) or in IPS neurons derived from patients with AD ( Young et al, 2018 ), but only on the background of preexisting intraneuronal pathology.…”
Section: Discussionsupporting
confidence: 76%
“…We also found that plasticity genes were downregulated in female compared with male APP/PS1 mice, suggesting that the accelerated Aβ pathology in females likely disrupts the expression of plasticity‐related proteins (PRPs), leading to the accelerated decay of LTP and memory in females compared with males. The downregulation of PRPs could be due to alterations in the function of NMDA and AMPA receptors, as sex differences are found in synaptic glutamate signalling (Mota et al, 2014; Qu et al, 2020; Wickens et al, 2018). An increase in glutamate levels severely affects AD males compared with females as they exhibit lower levels of GluA2‐containing AMPA receptor subunits (Wickens et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although AMPARs are implicated in both MS and AD, no major breakthroughs in treatment options have yet emerged, although understanding of the influence of AMPAR subunit composition has fuelled speculation that directed drugs, such as agonists of the plasticity-promoting GluA1-containing AMPARs ( Qu et al, 2021 ), may have therapeutic value. Similarly, selective antagonism of Ca 2+ -permeable AMPARs may be beneficial since they likely mediate AMPAR contributions to neurodegeneration ( Weiss, 2011 ).…”
Section: Discussionmentioning
confidence: 99%